PENGEMBANGAN USAHA LAYANAN JASA SERVIS AMBON JAYA MOTOR DI DESA PATEGUHAN-PANDAAN-PASURUAN - Mulyadi, -; Iswanto, - (Universitas Negeri Yogyakarta, 2017)
Pateguhan village located in the district Pandaan, Pasuruan, ± 20 km from Campus II University of Muhammadiyah Sidoarjo. Pateguhan village is densely populated residential area which is close to the industrial regions. So the average of them are employees of the factory. As a means of transportation every day they mostly use motorcycles. Seeing the condition of the area as the partners established a workshop service of motorcycles and motorcycle parts sale. Obstacles faced Options are limited keyequipment, no hydraulic tools Overhaul Part Crankshaft and unavailability Back Lift Motor Cycle so that when the disassembly of spare parts of motorcycles require a long time and is not ergonomic, Marketing conducted from mouth to mouth and get a close friend so less known. The absence of financial accounting income and expenditure so it is unknown the profit and loss of the work done. Viewed from the condition required a solution that is made of hydraulic tools Overhaul Part Crankshaft Motorcycle And Back Lift Motor Cycle and implementation, held financial accounting training conducted on UMKM, then created a brochure and banner marketing and implementation. Repair of these solutions is expected to Ambon Jaya Motor added increased revenue